Impact of Structured Training on Football Agility in Under-15 Players: A Comparative Analysis - Okilanda, Ardo; Orlando, Rafel; Arisman, Arisman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The objective of this research is to examine the impact of organized training interventions on the football agility of under-15 players at SSB Muspan. The main goal is to compare the Football Agility Score (FAS) values obtained from initial and post-training evaluations, taking into account various agility dynamics, real-world significance, and personalized reactions. Participants were subjected to a thorough agility assessment both before and after a predetermined training program, during which distances and timings were measured and recorded. The FAS, determined by multiplying the ratio of distance to time by a fixed factor, was used as a precise quantitative indicator of agility. The research used rigorous analysis to reveal the subtle effects of the training program on agility, taking into account characteristics such as quick changes in direction, acceleration, and deceleration. The comparison research showed a significant rise in post-training FAS values, suggesting a beneficial impact on participants' football agility. The results provide valuable practical knowledge for coaches, trainers, and sports scientists, emphasizing the need for customized training regimens that take into account individual reactions and agility dynamics. This research adds to the wider discussion in sports science by providing detailed insights on how to improve football agility in the specific age group of under-15s.